2021
DOI: 10.22225/jhp.8.1.2021.65-69
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Pancasila Value for Generation Z in Technology Development

Abstract: As the ideology of Indonesia, the existence of Pancasila is not without any challenges. In the development of science and technology, the existence of Pancasila is full of struggles. One of the challenges is the rapid social development that have happened nowadays has brought some changes in social activities. These social changes are marked by the development of the generation based on the needs for science and technology. Generation Z nowadays is known as the most active in their activities that depends on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
1
0
0
Order By: Relevance
“…8), the majority of answers demonstrate that surfing internet websites and social media platforms is important to Generation Z; representing 86.4%, whilst the minority of answers disagreed on that question; representing only 2.3% and only 11.3% answered to some extent. These findings are consistent with the study of Manurung & Monny (2021), which affirmed that technology has a major importance to Generation Z and influences on their personality and mindset. On the other hand, the study of Benavides, et al (2023) 9) demonstrates that Generation Z favourite social media application is Instagram; representing 25.1%, followed by Facebook; representing 17.5%, followed by TikTok; representing 14.2%, followed by Youtube; representing 12.9%, followed by Twitter; representing 12.6%, followed by Linkedin; representing 9.7% and finally came Snapchat; representing 8%.…”
Section: Section Two: Analysing Digital Characteristics Of Generation...supporting
confidence: 91%
“…8), the majority of answers demonstrate that surfing internet websites and social media platforms is important to Generation Z; representing 86.4%, whilst the minority of answers disagreed on that question; representing only 2.3% and only 11.3% answered to some extent. These findings are consistent with the study of Manurung & Monny (2021), which affirmed that technology has a major importance to Generation Z and influences on their personality and mindset. On the other hand, the study of Benavides, et al (2023) 9) demonstrates that Generation Z favourite social media application is Instagram; representing 25.1%, followed by Facebook; representing 17.5%, followed by TikTok; representing 14.2%, followed by Youtube; representing 12.9%, followed by Twitter; representing 12.6%, followed by Linkedin; representing 9.7% and finally came Snapchat; representing 8%.…”
Section: Section Two: Analysing Digital Characteristics Of Generation...supporting
confidence: 91%
“…According to [13], Pancasila is a reflection of the educational character in building the national identity of Indonesia as a great nation, modern, dignified and civilized. [14] added that Pancasila is also the guidelines for people to act and have to be understood and implemented in daily life. [15] argued that at the college level, the students need to grow up in their environment to learn empathy, sharing, rationality, spirituality, technological competency, communication skills etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pancasila is a reflection of the educational character in building the national identity of Indonesia as a great nation, modern, dignified and civilized. [6] At the college level, students need to grow in their environment to learn how to feel empathy for others, to share, to learn rationality, spirituality, competence in technology; as well as communication skills, and other fields that will support their life in society. Pancasila is also the guidelines for people to act and have to be understood and implemented in daily life.…”
Section: Introductionmentioning
confidence: 99%
“…Religion Education is education to foster students' physical and spiritual as well as the formation of students' personalities. He concluded that Religion Education is a complete process carried out in order to realize a complete human being who believes and fears to God Almighty [6]. From this formulation there are noble values in the form of spiritual values, humanity, personality, so that all of them prepare students to become good human beings and have moral values that are embraced in their lives in society.…”
Section: Introductionmentioning
confidence: 99%